Subsynchronous resonance in series compensated networks with high penetration of renewable energy sources - Chikohora, Tinashe Edward (Department of Electrical Engineering, 2022)
The global shift towards clean energy has seen a spiked rate of environmentally friendly renewable energy sources (RES) as utilities and regional energy blocks battle with rising demand. RES sites may be located in remote or populated areas with limited servitudes. To reduce investment costs, grid impact study assessments conducted by utilities often recommend new power plants to cut-in nearby existing lines for power evacuations after considering availability of wayleaves and other socio-economic concerns. There are foreseen and planned connections of RES evacuating power via series compensated lines in Africa. However, integrating RES through series compensated lines results in subsynchronous resonance (SSR) between generator rotors and the grid. SSR is a phenomenon where there is exchange of electrical energy between the generator shaft system and the transmission system below the fundamental power frequency leading to electrical instability. The future trend in power systems entails deeper investments of the same highlighted SSR inducing sources such as series compensation. This brings uncertainty and misperceptions in respect to effective management of the SSR problem translated to a case of either retarding power system investment without SSR against reinforcing grid investments with SSR inducing consequences. The dissertation dissects the SSR problem with emphasis on its management in a modern power system environment receiving rising RES and flexible alternating current transmission systems (FACTS) connections through series compensated lines. The simulations performed in this study utilised the IEEE first benchmark model (FBM) within Digital Simulation and Electrical Network – PowerFactory (DIgSILENT) software. The unmodified FBM served as a base case representation of the power system without RES or STATCOM (static synchronous compensator) penetrations. The various modifications to the FBM captured multiple scenarios representative of rising penetrations of wind power, solar power and static compensators. The generator, shaft, busbar terminals and series capacitor were monitored and analysed to derive SSR modulated torsional effects after applying a 3-phase fault to the system for 75 milliseconds. From the perspective of conventional synchronous non–renewable generation, decrease in SSR probability is achievable by adding RES like solar PV power in the vicinity. Another output from the simulations confirmed that PV generation does not participate in SSR occurrence as seen by its pre and post fault conditions recovering immediately and remaining constant afterwards. In addition, the results from the modal analysis comparison reinforced that as more RES or STATCOM devices are connected to the FBM, the overall system improves on oscillatory stability as seen by the oscillatory eigenvalue real parts becoming more negative and the damping ratios more positive. The future work involves analysis of SSR in other RES and how SSR protection can be incorporated in protection relays using a filtering method based on the prony analysis.